HISTORIOGRAPFY OF THE STUDY OF THE ARTISTIC LEGASY OF E. KONTRATOVYCH - БЕЛІЧКО, Н. Ю.; ЧЕЙПЕШ, А. І. (Art and Design, 2022)
Purpose: To analyze the sources that cover the historical events of Transcarpathia in the early XX century, the sociocultural center where the artist was formed, as well as the work and life of E. Kontratovych. Methodology. In the research, the following methods were used: the analytical method to identify the stage of development of the topic, the systematization method to process the collected information and to divide it into categories according to the available material and chronological order, and the method of generalization, which allowed to draw conclusions to this article. Results. The analysis of the sources, which illustrate the creative heritage and the life journey of E. Kontratovych (1912–2009), the representative of the Transcarpathian school of painting, was carried out. The available information was ordered chronologically — pre-Soviet (1930–1946), Soviet (1946–1990), and modern (since 1991) sources. Each group was organized according to the types of printed products — from monographs to periodicals. A separate group consists of archive materials that contain the important data for the reconstruction of both the environment where the creative personality of the artist was formed and the life of E. Kontratovych. The following materials were taken into account: the sources, which reveal the historical destiny of the territory of modern Transcarpathia; the publications devoted to the process of formation of the cultural and artistic environment in Uzhhorod city, and the materials with an analysis of the life and creative path of E. Kontratovych. The scientific novelty is that for the first time, the vast majority of sources, which highlight the important facts from the life of E. Kontratovych or analyze his creative work, were collected and systematized in one research. Practical significance. The presented materials, analysis of the found sources, and conclusions can be used in the scientific researches devoted to the Transcarpathian school of painting and fine arts of Ukraine of the XX century.